THE MANIFESTATIONS OF PERSON’S BEHAVIOR STRATEGY PRECONDITIONED BY MANAGEMENT INFLUENCE - Karapetyan , N. I. (Արդի հոգեբանություն, 2018)
The article is devoted to the disclosure of the relationship between managerial influence and the choice of employee behavior strategy. It includes the outcomes of the research which were analyzed qualitatively and quantitatively. It examines four different management models of the organizations, represents the managing typical styles and staff coping strategies. It identifies the connection of the strategy selection between manager’s style and coping strategy depending on the effectiveness of the organization, its position in the labor market and corporative culture.